Clinical Results of the NUsurface® Meniscus Implant versus Non-Surgical Controls at 24 months: Data from a Pooled cohort of a randomized controlled study and single arm study. Issue 7 (31st July 2020) - Alley, R; Alfred, Richard; Edelson, Richard; Greenleaf, Jonathan; Gersoff, Wayne; Gomoll, Andreas; Kaeding, Christopher; McKeon, Brian; Zaslav, Kenneth
Objectives: To demonstrate comparative KOOS outcomes (Symptoms, Pain, ADL, Sports/Rec, QoL, and Overall) of a synthetic meniscus implant versus non-surgical controls in treatment of persistent post meniscectomy knee pain. Methods: 242 patients enrolled in a pooled population, randomized controlled trial (RCT) and single-arm study, comparing the investigational device to non-surgical standard of care. Of the first 100 patients enrolled, whose follow-up has exceeded 24 months, 65 patients were treated with the meniscus implant, and 35 were treated non-surgically (Table 1). Validated KOOS scores at baseline, 6-week, 6-month, 12-month, and 24-month time points were obtained from all patients where a "clinically significant improvement" was considered to be an increase of 20 KOOS points, based on Roos et al., (2003). The investigational and control cohorts were compared at each time point using a two tailed t-test. All baseline cohort comparisons of demographics and KOOS scores were not statistically different (p>0.05). Results: Improvement in KOOS Pain for the investigational vs control cohorts at 6-months was 25.0 vs 10.5 points at 6-months, 31.1 vs 14.5 points at 12-months, and 29.5 vs 13.6 points at 24-months, respectively (Figure 1). Similarly, improvement in KOOS Overall for investigational vs controls was 23.3 vs 8.0 points at 6-months, 29.2 vs 11.4 points at 12-months, and 29.1 vs 13.4 points at 24-months, respectively. These data show a statistically significant improvement, above the clinically meaningful threshold, in the investigational arm versus the control arm as early as 6 months (p<0.001) and continues through the 12-month timepoint (p<0.001) and the 24-month timepoint (p<0.001). At 24 months, 5 (7.7%) investigational vs. 5 (14.3%) control patients were no longer qualified to remain in the study, and deemed study failures, due to removal of the investigational device, and due to non-surgical control patients receiving surgical intervention (Table 1). Adverse event analysis showed that at 12 months, more patients progressed to advanced knee reconstructive procedures in the non-surgical, control group (n=4, 11.4%) than in the surgical, investigational group (n=2, 3.1%). Conclusion: Early results of effectiveness using KOOS subscales and KOOS overall are encouraging. The investigational treatment showed statistically different outcomes, above the clinically important threshold, at 6, 12 and 24 months compared to non-surgical controls. The clinical study is ongoing, with long-term results to be reported in the future. Table 1. Numbers are patients available to complete the KOOS questionnaire; Numbers in parentheses are percentages of the baseline population Investigational 61 (Randomized Controlled Trial) 115 (Single Arm) Non-Surgical Controls 66 (Randomized Control Trial) Total Patients at Baseline 65 35 100 Patients at 6 weeks 58 (89%) 33 (94%) 91 (91%) Patients at 6 months 63 (97%) 32 (91%) 95 (95%) Patients at 12 months 60 (92%) 29 (83%) 89 (89%) Patients at 24 months 59 (91%) 28 (80%) 87 (87%) Figure 1.